Lactate – from villain to guardian - Marek Nalos (Indonesian Nutrition Association, 2023)
Elevated plasma lactate level is a useful warning sign in patients presenting with a variety of critical illnesses. Our understanding of hyperlactatemia, however, has improved and we can no longer associate lactate itself with any harmful effects. Lactate is a crucial intracellular buffer, and a central molecule in the interorgan exchange of carbon and redox potential. While lactate levels correlate with severity of acidaemia in shock there is little evidence to support the commonly held view that its origin is mainly secondary to anaerobic metabolism because of reduced tissue oxygen delivery.